Online education? Think again - Abdul Razak, Dzulkifli (SUN MEDIA CORPORATION SDN BHD, 2020)
Of late, we have been hearing the word “online” bandied about frequently, thanks to the Covid-19 pandemic. It may well be true for commercial sectors transacting tangible and material stuff but not so for others dealing in intangibles. Education in its true sense is one of them.